Opimal Unilateral Climate Policy with Carbon Leakage at the Extensive and the Intensive Margin - Peter Kjær Kruse-Andersen; Peter Birch Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2021)
We analyse the optimal design of unilateral climate policy in an open economy where the government is committed to a target for reduction of domestic CO2 emissions but where it is also concerned about carbon leakage. We highlight the importance of distinguishing between leakage at the extensive margin where firms relocate to a foreign country to avoid the domestic carbon tax, and leakage at the intensive margin where domestic firms lose world market shares to foreign competitors due to the tax. Assuming that the government cannot implement border carbon adjustments, we show that the optimal allocation can still be implemented through a combination of taxes on emissions, taxes on domestic consumption of energy and final goods, an output subsidy as well as a lump-sum location subsidy to leakage-exposed firms, subsidies to carbon capture, taxes on domestic production of fossil fuels, and a subsidy to domestic production of green energy. Simulation experiments indicate that the social welfare gain from implementing the optimal leakage-adjusted tax-subsidy scheme rather than a single uniform emissions tax could amount to 0.5 percent of national income. A location subsidy aimed at reducing leakage at the extensive margin contributes to reducing the welfare loss from leakage.
Keywords: H21; H23; Q48; Q54; 330; carbon leakage; optimal carbon taxation in an open economy